Image-guided high-dose-rate intracavitary brachytherapy technique for nasal keloid – a case report - Huang, Cheng; He, Mingyuan; Zhao, Hongfu; Cheng, Guanghui (Journal of Contemporary Brachytherapy, 2018)
The aim of this study is to report an uncommon case of nasal keloid treated with adaptive image-guided high-dose-rate (HDR) intracavitary brachytherapy. A 34-year-old female presented with nasal keloid after facial trauma was treated with scar resection and HDR intracavitary brachytherapy with a customized eccentric applicator. The total dose was 21 Gy in 6 fractions. During 3 years of follow-up, there was no evidence of recurrence at the local site, and no complications. In conclusion, HDR intracavitary brachytherapy is an effective way to prevent the recurrence of nasal keloids post-surgery.